HISTOLOGICAL CHANGE OF THE HEMOСAPILАRIES OF HIPPOCAMPUS IN EXPERIMENTAL THERMAL TRAUMA - Литвинюк, С.О. (World of Medicine and Biology, 2012)
In experiment on white rats histological condition of blood capillaries of hippocampal was studied after thermal trauma. . Severe burns were determined to cause considerable morphofunctional changes in the hemoсapilаries of hippocampus, the degree of damage depends on the terms of the experiment. Compensatory-adaptable processes in the blood capillaries are observed in the early stage after thermal injury, serious irreversible destructive changes are observed at the 14th end especially 21th days.
Keywords: hemoсapilаries; hippocampus; thermal trauma; histological changes